The Impact of Social Media On The Use of English Slang - Fadia Mahardika (UMBanjarmasin, 2024)
The proliferation of social media has significantly influenced the use of British slang among young people, regardless of their educational background. This study examines how social media facilitates the rapid spread of slang, making it a prevalent trend among teenagers. The method used is descriptive qualitative in the form of interviews where 2 participants from different backgrounds are taken. the first participant is someone who is an English student, while the second participant is an ordinary person who has no basic English. The findings showed that, although both participants recognized common acronyms such as